Respon Street Artist Akan Label Vandalisme yang Dilekatkan Pada Karyanya: Sebuah Kajian Kriminologi Budaya - Theresia Aurellia (Jurnal Kriminologi Indonesia, 2014)
This study gives an explanation about the struggle done by Jakarta street artists as a member of a subculture which is marginalized by negative labels made by legal authority and afterwards giving benefits to the corporation, to defend their cultural meaning and the essence of their culture. Drawing upon cultural criminology, this research uses qualitative approach with a field research method in order to directly understand the contested image, meaning, and representation within the placement of their piece. In the end, this research found the reclaiming of public place as their response towards the vandalism label and to strive against the various of interest which keep marginalizing them from public space.